دور رقمنة النظام الضريبي في تحسين مردودية التحصيل الجبائي في ظل الإصلاحات الضريبية في الجزائر - حداش امال (جامعة البليدة2؛كلية العلوم الاقتصادية العلوم التجارية وعلوم التسيير, 2024)
This study aims to highlight the role of tax system digitization in improving tax collection efficiency in Algeria, within the framework of the state's efforts to reform and modernize the tax system, promote regular taxation, and gradually replace oil-based revenues. The study includes a theoretical part that explores various concepts related to tax reform and collection, presents the general framework for the digitization of tax administration, and delves deeper into the topic through a detailed analysis of the electronic tax system "Jibayatic." Additionally, it evaluates the impact of digitizing tax administration on improving tax revenues using an analytical approach based on several indicators. On the practical side, 200 questionnaires were distributed to employees of the tax administration and users of the electronic tax system in the Directorate of Large Enterprises as well as the Roubia and Bouira tax centers. The findings reveal that implementing digitization at the directorate and the two tax centers has had a significantly positive impact on enhancing tax collection efficiency. The results indicate that the adoption of the electronic tax system has strengthened the effectiveness of the tax administration, improved the quality of services provided to taxpayers, introduced greater transparency in transactions, and helped reduce tax-related corruption. Furthermore, the system contributed to lowering tax collection costs, increasing regular tax revenues, and enhancing oversight mechanisms to combat tax evasion and fraud. Based on these results, several recommendations were made, the most important of which is the need for continuous on-the-ground monitoring to accelerate the implementation of this system and generalize its use across all tax administrations by addressing the obstacles it faces and seeking optimal solutions to avoid further delays Key words: Digitization - Electronic Tax System - Tax Collection - Tax
دراسة ميدانية
Keywords: الرقمنة; النظام الجبائي الكترو; التحصيل الجبائي